2020
DOI: 10.1093/iob/obaa033
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transcriptional Mechanisms Respond Rapidly to Ecologically Relevant Thermal Fluctuations During Temperature-Dependent Sex Determination

Abstract: An organism’s ability to integrate transient environmental cues experienced during development into molecular and physiological responses forms the basis for adaptive shifts in phenotypic trajectories. During temperature-dependent sex determination (TSD), thermal cues during discrete periods in development coordinate molecular changes that ultimately dictate sexual fate and contribute to patterns of inter- and intra-sexual variation. How these mechanisms interface with dynamic thermal environments in nature re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…Nest thermal environments in nature are often more dynamic than those implemented in artificial incubation experiments (Paitz et al, 2010;Bowden et al, 2014;Bock et al, 2020a). In this study, we found that fluctuating thermal regimes yielded different outcomes from the constant temperature control for a subset of hatchling traits.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Nest thermal environments in nature are often more dynamic than those implemented in artificial incubation experiments (Paitz et al, 2010;Bowden et al, 2014;Bock et al, 2020a). In this study, we found that fluctuating thermal regimes yielded different outcomes from the constant temperature control for a subset of hatchling traits.…”
Section: Discussionmentioning
confidence: 67%
“…Mounting evidence suggests that thermal fluctuations in wild nests play key roles in shaping offspring sex ratios in other TSD species, such as Trachemys scripta (Carter et al, 2018); yet we currently lack an empirically validated model to predict crocodilian sex ratios under fluctuating thermal regimes. This is in part because few experiments have implemented incubation treatments that incorporate thermal variability in these taxa (Simoncini et al, 2019;Bock et al, 2020a) and because the molecular mechanisms underlying TSD remain elusive, despite recent advances in this area (Czerwinski et al, 2016;Yatsu et al, 2016;Deveson et al, 2017;Ge et al, 2018). Predicting the impacts of thermal fluctuations on crocodilian sex ratios is further complicated by their unique temperature-bysex reaction norm, in which females are produced at extreme temperatures and males at intermediate temperatures (F-M-F pattern) (Lang and Andrews, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research suggests that temperature-responsive epigenetic regulators initiate sex-specific gene expression in reptiles [47] and may drive sex determination in species with TSD. The histone demethylase Kdm6b has received specific attention in this regard, as it is among the earliest genes to respond to temperature [8,9]; in T. scripta , cool, male-producing temperatures result in increased expression of Kdm6b [5].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of temperature on Kdm6b expression is regulated by signal transducer and activator of transcription 3 (STAT3), where levels of phosphorylated STAT3 increase at warm temperatures, repressing Kdm6b transcription [6]. For several species with TSD, including T. scripta , an intron-containing transcript of Kdm6b accumulates at cool incubation temperatures [7,8,10]. More generally, intron retention has been demonstrated for a number of genes in the developing gonads of species with TSD [712], including the American alligator ( Alligator mississippiensis ), where Jarid2 exhibits intron retention that can change over the course of hours when incubation temperatures fluctuate [7].…”
Section: Introductionmentioning
confidence: 99%